Religious and Ethical Issues of Artificial Intelligence: Expert Assessments and the Vatican Position - A. A. Abramov (Концепт: философия, религия, культура, 2020)
The paper is dedicated to the emergence of progressive artificial intelligence technologies and its relations to the human nature and soul, as viewed by experts and in such specific community as the church. We seem now to be entering a new phase of the comprehension of the moral aspects of the introduction of artificial intelligence (AI) into the life of different societies. The romantic period of high expectations and excessive anxiety is replaced by the growing understanding of the complexity of the man‒machine interaction, which implies the intersection moral, legal, political and utilitarian dimensions of both a person and an artifact. The problematic issues are now more obvious, clear and difficult, as the disciplinary boundaries are revealed and highlighted. Among the crucial issues one should mention deficiencies in definitions; weakness of research optics and the vision that would be friendly to other areas of study or practice. This also includes the issues of integral assessment of the existing dangers, difficulties in describing the mechanisms of fulfilling both ethical and technically viable requirements. As scientific knowledge accumulates, both the benefits of introducing AI technologies into everyday life and previously underestimated new threats become more obvious. These societal and humanitarian ones include, in particular, social turbulence, neuroticism, digital crimes and crimes associated freedom abuses and losses of identity. Over the past few years, state and non-governmental institutions have proposed different approaches to determining what is included in the moral core of the problem under consideration. The efforts of many, if not most, of them turn out to be compromised by suspicions in willful intents. In this context, the broad consensus with the key agent facilitators is required, and the role such actors play in providing social stability is indisputable. One of the key roles in offering society the broadest vision on the anthropocentric development and AI progress belongs to the Roman Catholic Church. The Vatican’s quest to unite philosophers, AI developers, and religious leaders to address the ethical challenges of designing and implementing robotics is becoming an important element of the Christian witness in a world that is consider ed irrevocably secularized by many.